Uterine Development During Induced Puberty in Girls with Turner Syndrome - Obara-Moszynska, Monika; Dzialach, Lukasz; Rabska-Pietrzak, Barbara; Niedziela, Marek; Kapczuk, Karina (Frontiers in Endocrinology, 2021)
Objective: Most girls and women with Turner syndrome (TS) require estrogen replacement therapy (ERT) to initiate or maintain pubertal development. Most likely, the most fundamental effect of ERT in hypogonadism is the promotion of uterine growth. The optimal ERT model is still being discussed. The present study aimed to assess uterine size in girls with TS in the prepubertal state during and after the induction of puberty and compare it to a healthy population. Methods: The analysis encompassed 40 TS girls. The prepubertal and postpubertal control groups contained 20 healthy girls each. All patients with TS were treated with 17-ß estradiol. Uterine imaging was performed with two-dimensional (2D) transabdominal ultrasound. The uterine volume (UV) and fundocervical antero-posterior ratio (FCR) were calculated in patients with TS before the pubertal induction, after 6-12 months of estrogen replacement therapy (ERT), after ≥ 36 months of ERT or ≥ 12 months after menarche. Results: The average age of TS patients at estrogen introduction and at the last control visit, when the uterus was considered mature, was 12.9 years and 16.1 years, respectively. The UV in patients with TS at the beginning of ERT was 1.55 ± 1.22 cm3 and was not significantly different from the UV in the prepubertal controls. The mature UV in patients with TS was 31.04 ± 11.78 cm3 and was significantly smaller than the UV of the postpubertal controls (45.68 ± 12.51 cm3, p<0.001). The FCR in girls with TS did not differ significantly from that in the prepubertal and postpubertal control groups, respectively. No prognostic factors could be established for the final UV. By the last control visit, thelarche had advanced in most patients to Tanner 4 and 5 (37.5% and 40%, respectively). Conclusions: Before the onset of ERT, patients with TS have a uterus similar in size to that in prepubertal healthy girls. Pubertal induction in patients with TS causes a significant increase in the UV that is detectable after 6-12 months of ERT. The mature uterus is smaller in patients with TS than in the age-matched healthy population.